Ossifying Subperiosteal Hematoma Caused by a Plexiform Neurofibroma. Issue 1 (6th November 2020) - Van den Berge, Steven; Declercq, Hugo; Pans, Steven
Teaching Point: Subperiosteal haemorrhage is a rare complication of a plexiform neurofibroma which may mimic a malignant peripheral nerve sheath tumour.